Extracondylar patellar dislocation inverted on the vertical axis in a collegiate football athlete: A case report and literature review - Roberts, J. C.; Zegan, A. M.; Fink, A. D.; Kubala, J. M. (International Journal of Athletic Therapy & Training, 2024)
A male, Division II collegiate football player presented with an extracondylar lateral patellar dislocation with inversion of the patella on its vertical axis following impact with the ground on the medial side. The patient was sedated for closed patellar reduction. He returned to full participation after 6 weeks of a progressive strength program. Extracondylar patellar inversion is not often associated with severe force or a direct blow, but the case described occurred after a high-impact tackle to the ground. This is also the only published case of a collegiate athlete returning to collision sport after sustaining an inverted extracondylar patellar dislocation. Despite the deformity and emergent nature of an inverted patellar dislocation, having patients complete early mobilization activities, including range of motion, and aggressive strengthening and functional progressions may facilitate a quick and safe return to highly intensive and competitive physical activity.